Arthroscopic Remplissage for Anterior Shoulder Instability - Akshar V. Patel BS; Daniel Wagner MD; Parth A. Vaghani BS; David Gibbs BS; Noah Mallory BS; Vikas Munjal BS; Connor Hoge MD; Gregory L. Cvetanovich MD; Ryan C. Rauck MD (SAGE Publishing, 2024)
Background: There are several approaches such as the Bankart repair, Latarjet, and Remplissage to treat recurrent glenohumeral instability. Indications: We chose to augment an arthroscopic Bankart repair with a Remplissage in this 26-year-old patient given the presence of a Hill-Sachs lesion, history of recurrent shoulder dislocations, and young age of the patient. Technique Description: We established four portals using previously well-documented techniques. The Hill-Sachs lesion was evaluated using the anterosuperior portal. Two anchors were placed, one on both the superior and inferior aspects of the Hill-Sachs lesion. The sutures were shuttled through the knotless anchor mechanism and tensioned after confirming the cannula was through the deltoid. Then, we completed the Remplissage by repairing the infraspinatus tendon and capsule into the posterior humeral head. Results: The Remplissage procedure is very successful at reducing recurrent instability in young, active patients. Previous studies have reported very low rates, even 0% recurrent instability, after surgery with 80% to 90% of patients returning to sports. Studies have also documented excellent patient-reported outcomes at short- to mid-term follow-up. Complication rates are historically lower when the Remplissage is done with an arthroscopic Bankart repair than the Bankart repair alone. Discussion/Conclusion: The Remplissage procedure is a safe, effective option at reducing future instances of shoulder dislocations in conjunction with Bankart repairs. Patients can expect to return to their active lifestyles, with many patients achieving the same level of activity as before the initial shoulder dislocation. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.